Legal Approaches to Cybersecurity: A Global Study of Frameworks and Enforcement in the Digital Age - Ethan Tan; Rachel Chan; Daiki Nishida (Yayasan Adra Karima Hubbi, 2026)
Background. Cybersecurity is a critical global issue driven by increasing reliance on digital technology, which heightens vulnerabilities to data breaches and cyber threats. Public-private partnerships (PPPs) play a key role in strengthening cyber law enforcement, but challenges like regulatory gaps and differing priorities demand systematic collaboration to optimize their effectiveness. Purpose. This research aims to assess the role of public-private partnerships (PPP) in strengthening cyber law enforcement in various legal systems. Method. This research uses an approach Systematic Literature Review (SLR) to identify, analyze and synthesize various studies relevant to the topic of cyber law enforcement and the role of public-private partnerships (PPP) in that context. Results. The research highlights key themes including the effectiveness of PPPs in improving cybersecurity, barriers to their implementation due to regulatory and interest conflicts, regional differences in success rates influenced by legal systems, and the role of PPPs in fostering collaborative innovation and law enforcement, alongside recommendations for strengthening legal frameworks and addressing gaps in empirical data. Conclusion. This research highlights the critical role of public-private partnerships (PPPs) in cyber law enforcement, emphasizing that transparency, trust, and shared commitment are key factors influencing their effectiveness.